Cetacean strandings along the German North Sea coastline 1604–2017. (28th May 2021) - Christian Kinze, Carl; Czeck, Richard; Herr, Helena; Siebert, Ursula
Abstract: The occurrence of 19 cetacean species along the German North Sea coastline as well as the lower reaches of the major rivers discharging into the German Bight is reviewed for the period 1604–2017 based on records of dead animals, either stranded dead or put to death. The harbour porpoise ( Phocoena phocoena ) is considered the most abundant and only native species in German coastal and riverine waters. Based on written sources its presence can be traced back to at least 1651, although with statistical data only available from 1990. Finds of further 18 species have been documented: white-beaked dolphin ( Lagenorhynchus albirostris ), bottlenose dolphin ( Tursiops truncatus ), Atlantic white-sided dolphin ( Lagenorhynchus acutus ), common dolphin ( Delphinus delphis ), striped dolphin ( Stenella coeruleoalba ), Risso's dolphin ( Grampus griseus ), long-finned pilot whale ( Globicephala melas ), killer whale ( Orcinus orca ), beluga whale ( Delphinapterus leucas ), narwhal ( Monodon monoceros ), Sowerby's beaked whale ( Mesoplodon bidens ), northern bottlenose whale ( Hyperoodon ampullatus ), sperm whale ( Physeter macrocephalus ), minke whale ( Balaenoptera acutorostrata ), sei whale ( Balaenoptera borealis ), fin whale ( Balaenoptera physalus ), blue whale ( Balaenoptera musculus ) and humpback whale ( Megaptera novaeangliae ). This review corrects several false species assignments earlier introduced in literature based on incorrect scientific or ambiguous German vernacular names and recovers lost records of beluga whale, northern bottlenose whale, sperm whale and fin whale.